Results Of Analyses of Blast-Furnace Gases - Charles A. Colton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1878)
(Read at the Amenia Meeting, October, 1877.) THE results of a series of analyses extending over a period of three weeks at the Cedar Point Iron Company's furnace, Port Henry, New York, are given in Tables I and II. This furnace uses a very pure magnetite and Lehigh and Lackawanna anthracite. The flue leading the gas from the "down-comer" to the boilers was tapped by a a inch gas pipe, which carried the gas to the Orsat apparatus. The pressure of the gas not always being sufficient, owing to the small amount made, to force it into the apparatus, I omitted taking samples several days, and with the exception of the last three days of the campaign, made the analyses whenever opportunity offered. I find the Orsat apparatus, as described by Prof. Egleston,* to work very well, with one exception. The CO is not absorbed as readily in the ammonia-copper solution as he states in his description of the apparatus, as many as 50, and sometimes 60, passes being necessary to absorb all the CO. The power of absorbing rapidly increases as the solution is used, and this would indicate that the more oxygen it contains the quicker will it do the work. Probably the addition of a small amount of some oxidizing agent would remedy this. When the furnace was working in its normal condition, I had no occasion for using the filter, the amount of fume being so small as not to cause any inconvenience. The gas burned with the flame peculiar to CO, and contained just enough solid particles to give it a slight reddish tinge. * See Transactions, II, 226; V, 487, 621.